Strategies for Writing a Self-Study and Conducting a Site Review - Margaret A Thomas-Evans PhD; Carrie E Longley MFA; Mengie M Parker PhD (Academic Chairpersons Conference Proceedings, 2018)
This presentation will include a discussion of the principle components of a department self-study and provide examples from two departments (English and Fine and Performing Arts). The specific self-study structure we developed is especially beneficial for small university campuses that may need to justify programs or budgetary expenditures.
Keywords: department self-study; site visit; program review